Linktree-based digital media development to improve learning on the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in cosmetology education - Siti Wahida; Astrid Sitompul; Marnala Tobing; Asyiqaruzqi Fauziah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) curriculum implements innovative learning in the education sector's digitalization era. This program enables student exchanges and expands the boundaries of the physical classroom into a digital space. Linktree-based digital media can be used online by students participating in student exchange collaborations and by students studying in class. This research aims to determine the feasibility and effectiveness of Linktree-based digital media in improving MBKM learning in cosmetology education. The research uses the ADDIE development model. Validation results from learning experts reached 80.33% in the good category, while material experts scored 81.63% in the very good category. Media experts' validation scored 80% in the good category. The results of the limited trial reached 85.54% in the very good category, and field trials obtained 90.4% in the very good category. This demonstrates that Linktree-based digital media is feasible and effective for use in cosmetology learning to enhance MBKM learning. The pre-test score was 75.52%, and the post-test score was 88.62%, showing a significant increase of 16.10%. This data indicates improved learning outcomes and student motivation to participate in MBKM learning. The contribution of the research shows that using Linktree can enhance student learning outcomes by increasing motivation and engagement while also simplifying the delivery of learning materials for teachers, thus supporting the improvement of MBKM learning and increasing the accessibility of cosmetology education resources.